2016
DOI: 10.1021/acsnano.6b06293
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamically Reconfigurable Ambipolar Black Phosphorus Memory Device

Abstract: Nonvolatile charge-trap memory plays an important role in many modern electronics technologies, from portable electronic systems to large-scale data centers. Conventional charge-trap memory devices typically work with fixed channel carrier polarity and device characteristics. However, many emerging applications in reconfigurable electronics and neuromorphic computing require dynamically tunable properties in their electronic device components that can lead to enhanced circuit versatility and system functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 45 publications
1
106
0
1
Order By: Relevance
“…Also, numerous attempts have focused on the passivation via a relatively thick (10 nm or above) Al 2 O 3 layer grown on top of the BP flakes by ALD. 12,[22][23][24][25][26][27][28][29][30][31] Some attempts to reduce the thickness of the capping A 2 O 3 have also been reported. 32 Thin capping may simultaneously passivate and serve as a tunnel barrier (which may even lead to improved electrical contacts 33,34 ) representing a double advantage over thick capping in which electrical contacts must be patterned before passivation (ex-situ).…”
mentioning
confidence: 99%
“…Also, numerous attempts have focused on the passivation via a relatively thick (10 nm or above) Al 2 O 3 layer grown on top of the BP flakes by ALD. 12,[22][23][24][25][26][27][28][29][30][31] Some attempts to reduce the thickness of the capping A 2 O 3 have also been reported. 32 Thin capping may simultaneously passivate and serve as a tunnel barrier (which may even lead to improved electrical contacts 33,34 ) representing a double advantage over thick capping in which electrical contacts must be patterned before passivation (ex-situ).…”
mentioning
confidence: 99%
“…[51][52][53][54][55][56][57][58] Nonvolatile charge-trap memory is a popular type of solidstate memory technology that offers its excellent data storage performance and device scalability. In addition to these devices and modules operating with fixed characteristics, BP, being a promising layered semiconductor, has also been exploited for application in nonvolatile memory and circuits, which are regarded as critical components in many emerging electronic applications including neuromorphic computing, efficient data storage, as well as dynamically reconfigurable digital circuits.…”
Section: Exploring Bp For Memory Applicationsmentioning
confidence: 99%
“…[52,55,59] Compared with other 2D materials, for instance, MoS 2 , BP has the advantage of ambipolar transport characteristics. [52,56] For example, Li et al demonstrated nonvolatile floating-gate memories based on BP/h-BN/MoS 2 stacked heterostructure, with the few-layer BP, h-BN, and MoS 2 acting as the channel layer, tunnelling barrier layer, and charge trapping layer, respectively. [52,56] For example, Li et al demonstrated nonvolatile floating-gate memories based on BP/h-BN/MoS 2 stacked heterostructure, with the few-layer BP, h-BN, and MoS 2 acting as the channel layer, tunnelling barrier layer, and charge trapping layer, respectively.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the study of memristors as artificial synaptic devices has been gaining momentum since the discovery of the reversible resistive switching effect . Within this realm, recent developments of hybrid electrophotonic responsive devices may prove to be a leading indicator for the evolution of intelligent, artificial neuron‐based VPAs . Such systems were envisioned as being able to mimic the performance of biologic eyes without the need for external cameras or processors .…”
Section: Introductionmentioning
confidence: 99%